Facce: um framework para avaliar a carga cognitiva na educação - Falcade, Andressa (2021)
With the great advance in technology for education, one has to consider the way in which knowledge is offered in the digital spheres and its interference in student learning, since it only transposes the same resources from face-to-face teaching to online teaching. line does not match the needs imposed by this new modality. One of the aspects that can be considered for the qualification of online education is the cognitive load required for the presentation of content and the organization of technological environments, which is related to the mental effort of the student involved in the teaching and learning process. In this sense, the research problem was: What can help professors and institutions in identifying high cognitive loads and allow them to better balance them so that the student can reach the learning objectives in a more concrete way? With this in mind, the purpose of this thesis is: To implement the assessment of cognitive load in Education. To achieve this goal, first, an approximation of ideas and concepts was carried out in order to identify the convergences between the Cognitive Load Theory, the Cognitive Theory of Multimedia Learning, the Electronic Learning Guidelines and the Interface Usability Principles. From the identification of these convergences, it was possible to point out aspects for balancing the cognitive load in education, which are arranged in two categories: content presentation and organization of technological environments. Based on these aspects, two checklists were built in order to instrumentalize the assessment of cognitive load which, integrated with all the theoretical information studied, made up the FACCE Framework, hosted on the internet to ensure greater visibility of the tool. In order to identify evidence of the tool's quality, two evaluations were carried out. The first evaluation used the Cognitive Path technique, being applied with three experts in interface design in order to identify possible interpretation difficulties in using the Framework. Some of the inconsistencies identified in this assessment were changed in order to maintain regularity from one interface to another, improve the feedback presented and improve the readability of the information. The second evaluation was carried out with thirteen participants in a controlled environment, where they performed interactions with the tool through a previously stipulated script. At the end, they answered the SUS scale questionnaire, identifying problems related to Learning, Satisfaction, Errors, Memorization and Efficiency. After the analyses, the FACCE Framework reached 88.26 points, being classified as “best imaginable” among the quality levels of the usability of the interface. The results showed that the tool had good acceptance by those involved, being described as easy to use, easy to learn, with little or no errors or inconsistencies and good regularity between the interfaces. Finally, it is noteworthy that the participants claimed to have built new learning in the face of interaction with the tool and that they intend to use it frequently in their professional activities. With this, it is possible to conclude that the Framework has great potential among the target audience and can offer a better quality condition in the provision of education when used.